2021
DOI: 10.3324/haematol.2020.265991
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of T-cell lymphoma with T follicular helper phenotype by RHOA mutation analysis

Abstract: Angioimmunoblastic T-cell lymphoma (AITL) and peripheral T-cell lymphoma with T follicular helper phenotype (PTCL-TFH) are a group of complex clinicopathological entities that originate from TFH cells and share a similar mutation profile. Their diagnosis is often a challenge, particularly at an early stage, due to a lack of specific histological and immunophenotypic features, paucity of neoplastic T cells and prominent polymorphous infiltrate. We investigated whether the lymphoma associated RHOA Gly17Val (c.50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…However, the occult nature of the TFH cell proliferation in both LN specimens and the predominant clonal CTC proliferation/lymphoma at relapse suggest that the TFH cell proliferation might represent a smouldering AITL, or an early manifestation of AITL. 20 The impact of TET2 and DNMT3A mutations on the survival and expansion of B cells and T cells is unclear. Individuals with clonal haematopoiesis do not usually show peripheral blood lymphocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the occult nature of the TFH cell proliferation in both LN specimens and the predominant clonal CTC proliferation/lymphoma at relapse suggest that the TFH cell proliferation might represent a smouldering AITL, or an early manifestation of AITL. 20 The impact of TET2 and DNMT3A mutations on the survival and expansion of B cells and T cells is unclear. Individuals with clonal haematopoiesis do not usually show peripheral blood lymphocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…In case 2, the systemic dissemination of occult RHOA ‐G17V‐mutant TFH cells and their preferential distribution around HEVs surrounded by mild extrafollicular FDC hyperplasia in LNs would be compatible with AITL. However, the occult nature of the TFH cell proliferation in both LN specimens and the predominant clonal CTC proliferation/lymphoma at relapse suggest that the TFH cell proliferation might represent a smouldering AITL, or an early manifestation of AITL 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a recent study focusing on screening for the RHOA (G17V) mutation has demonstrated the relevance of mutation detection for the early diagnosis of PTCL with T-follicular helper (TFH) phenotype in specimens that showed no evidence of lymphoma after combined histological and clonality analyses. 9 Regarding our t-NGS approach, the pathogenicity of the mutations detected in samples with a negative PCR-based clonality might be questionable and raises the issue of clonal hematopoiesis (CH). Some of the genes included in our lymphoma panel have been shown to be related to CH (DNMT3A, EZH2, JAK2, TET2, TP53).…”
Section: Resultsmentioning
confidence: 99%
“…Occasionally, a negative result is observed: this can occur in cases of poor fixation or early neoplastic involvement, which turns out to be below the threshold of sensitivity of a conventional Sanger approach. Under the latter circumstances, a next-generation sequencing technique for TCR or recurrently mutated genes (see below) may provide evidence of the neoplastic nature of the process [ 24 ].…”
Section: Molecular Characteristicsmentioning
confidence: 99%